THE EFFECT OF GROUP COUNSELING SERVICES WITH BIBLIO-COUNSELING TECHNIQUES ON VERBAL BULLYING BEHAVIOR OF STUDENTS AT SMAN 4 PALU - Wardani; Durrotunnisa (Education Journal, 2021)
This study aims to explain the effect of group counseling on bibliocounseling techniques in reducing students' verbal bullying behavior. The subjects of this study were 6 students of SMAN 4 Palu. This research is a quantitative research, using a single group experimental design method (without comparison). The instrument used to collect data was a questionnaire. The data were processed and analyzed descriptively and inferentially using the Wilcoxon Sign Rank Test formula. The results showed that there were differences in verbal bullying behavior before and after being given bibliocounseling technique counseling services. Thus, group counseling services for bibliocounseling techniques are effective in reducing verbal bullying behavior of students at SMA Negeri 4 Palu.